2003
DOI: 10.1525/mp.2003.21.2.217
|View full text |Cite
|
Sign up to set email alerts
|

Musical Features That Facilitate Melody Identification: How Do You Know It's “Your” Song When They Finally Play It?

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. University of California Press Duke UniversityWhat information do listeners use to "Name that Tune"? This question was investigated in a two-phase experiment. In Phase 1, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
63
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 80 publications
3
63
0
Order By: Relevance
“…Experienced listeners are often able to recognize a melody within just a few notes (Dalla Bella, Peretz, & Aronoff, 2003;Schellenberg, Iversen, & McKinnon, 1999;Schulkind, Posner, & Rubin, 2003). The present study provides an examination of how this is accomplished.…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…Experienced listeners are often able to recognize a melody within just a few notes (Dalla Bella, Peretz, & Aronoff, 2003;Schellenberg, Iversen, & McKinnon, 1999;Schulkind, Posner, & Rubin, 2003). The present study provides an examination of how this is accomplished.…”
mentioning
confidence: 86%
“…Studies of melody identification (Hébert & Peretz, 1997;White, 1960), recall, and expectancy (Carlsen, 1981) have posited a contribution of musical distinctiveness without directly testing it. Schulkind et al (2003) examined the musical features that facilitate melody identification and, so, questioned what type of information (e.g., phrase boundaries, melodic interval, musical ornaments) contributes to melody recognition. In their study, 28 participants, who were not selected for musical training, identified 34 songs presented note by note.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Tonality is ubiquitous in Western music, and most listeners, either musically trained or not, can identify the most stable pitch while listening to tonal music [11]. Furthermore, this process is continuous and remains active throughout the sequential listening experience [72].…”
Section: Feature Extractionmentioning
confidence: 99%